Patterns of acoustic phenology in an anuran assemblage of the Yungas Andean forests of Argentina - Martín Boullhesen; Marcos Vaira; Rubén Marcos Barquez; Mauricio Sebastián Akmentins (Acta Herpetologica, 2023)
Breeding seasons in anurans are usually noticed by their advertisement calls, which stand as the main signal emitted by males during their adult life. These calls are species-specific signals with multiple information and can be used to monitor anuran populations over extended time periods. Applying a Passive Acoustic Monitoring method (PAM), we described the acoustic breeding phenology of an anuran assemblage along an altitudinal elevation range in the Yungas Andean forests of Argentina. In addition, we propose a new classification scheme for their acoustic phenological strategies, based on the male’s calling records throughout an entire year. Also, we assessed the temporal and spectral niche overlap by the anuran species recorded. The assemblage was active throughout the entire year, with a higher concentration of calls recorded during the spring-summer season. We describe five distinct Acoustic Breeding Strategies based on the calling patterns of the recorded species. Temporal niche overlap was higher in the spring-summer season and in the lowest study site. The use of a PAM as a tool to monitor the advertisement calls in anurans communities could be a reliable technique to obtain different information about the species’ acoustic phenology and the temporal use of the acoustic communication channel.